Frontotemporal Lobar Degeneration: Current Concepts in the Light of Recent Advances - Kumar‐Singh, Samir (Brain Pathol, 2007)
Work done over the past decade has led to a molecular understanding of frontotemporal lobar degeneration (FTLD), a deadly disease that afflicts patients in mid‐life. It is a common cause of dementia, second only to Alzheimer’s disease in the population below 65 years of age. Neuroanatomical and neurobiological substrates have been identified for the three major subtypes of FTLD and these discoveries have broadened the FTLD spectrum to include amyotrophic lateral sclerosis (ALS). Mutations in MAPT were found to cause frontotemporal dementia and parkinsonism linked to chromosome 17 (FTDP‐17), a familial disorder with filamentous tau inclusions in nerve cells and glial cells. FTDP‐17 can result in clinical syndromes that closely resemble progressive supranuclear palsy, corticobasal degeneration and Pick’s disease. More recently, mutations in three genes (VCP, CHMP2B and PGRN) have been found to cause FTLD with ubiquitin‐positive, tau‐negative neuronal inclusions (FTLD‐U). They explain a large proportion of inherited FTLD‐U. It remains to be seen whether dementia lacking distinctive histopathology (DLDH) constitutes a third disease category, as many of these cases are now being reclassified as FTLD‐U. Recently, TAR DNA‐binding protein‐43 (TDP‐43) has been identified as a key protein of the ubiquitin inclusions of FTLD‐U and ALS. Thus, for familial forms of FTLD and related disorders, we now know the primary etiologies and accumulating proteins. These findings are pivotal for dissecting the pathways by which different etiologies lead to the varied clinicopathological presentations of FTLD.